The Influence of Transparency and Accountability on Muzakki's Trust in Baznas Malang - Istutik, Istutik; Wachid, Nahdliah Mafaza; Tuakia, Hedher (Assyarikah: Journal of Islamic Economic Business, 2025)
This study aims to analyze the effect of transparency and accountability on the trust of muzakki in distributing zakat through BAZNAS Malang City. The type of research used is quantitative, with primarydata collection through distributing questionnaires. The study population consisted of muzakki who distributed their zakat to BAZNAS Malang City during 2022, with a total of 214 people. Determination of the number of samples using the Slovin formula, obtained a sample of 68 respondents. Data analysis was carried out using multiple linear regressions to test the effect of transparency and accountability variables on muzakki trust. The results showed that transparency and accountability had a positive and significant effect on muzakki trust in distributing zakat through BAZNAS Malang City. The Adjusted R-square value obtained was 0.713 indicating that 71.3% of the variation in muzakki trust can be explained by the transparency and accountability variables. This finding emphasizes the importance of BAZNAS Malang City to continue to maintain and improve the level of transparency and accountability in zakat management, as an effort to increase muzakki trust. Thus, it is hoped that the amount of zakat distribution from muzakki will increase, which in turn can have a positive impact on people in need, especially mustahiq.